Super Rabbit Boy's team-up trouble! - Flintham, Thomas (New York : Scholastic Inc., 2021)
When King Viking, Miss Business, and their henchmen team up to cause trouble, Super Rabbit Boy and Mega Mole Girl also join forces, but will they be able to work together to save the world?
K-3
530L
2.8
Keywords: Superheroes -- Juvenile fiction; Supervillains -- Juvenile fiction; Animals -- Juvenile fiction; Video games -- Juvenile fiction; Superheroes -- Fiction; Supervillains -- Fiction; Animals -- Fiction; Video games -- Fiction; Animal fiction; Superhero fiction